Comparative Analysis Of Green Accounting Practices Of Indonesian Companies (Case Study Of Service Companies And Trading Companies 2020-2022) - Fadilla Ardhyanita; Fista Apriani Sujaya; Meliana Puspitasari (International Journal of Management, Economic, Business and Accounting, 2024)
Purpose of the study — The purpose of this study is to compare awareness, responsibility, reporting, and environmental audits in service companies and trading companiesResearch method — This study uses a comparative hypothesis test conducted using an independent sample test or independent variable difference test with the Mann Whitney U-test. The data processed is non-parametric statistics. The research subjects are 16 service companies and 16 trading companies listed on the Indonesia Stock Exchange for the period 2020-2022.Result— The results of this study indicate that in testing in 2020 and 2021 there are no differences in green accounting awareness, green accounting responsibilities, green accounting reporting, and environmental audits in service companies and trading companies. In 2022, there are no differences in green accounting awareness, green accounting responsibilities, and green accounting reporting in service companies and trading companies, but there are differences in environmental audits.Conclusion— The application of green accounting is expected to be able to meet the needs of companies in identifying and presenting information related to social and environmental responsibility. The findings suggest that service companies and trading companies have similar practices in green accounting awareness, responsibilities, and reporting, but differ in environmental audits in 2022.